Transition Metal Complexes of 1, 4(2'-Hydroxyphenyl-1-yl) di-imino azine: Synthesis, Characterization and Antimicrobial Studies - M. Revanasiddappa; T. Suresh; Syed Khasim; S. C. Raghavendray; C. Basavaraja; S. D. Angadi (E-Journal of Chemistry)
The synthesis and characterization of first row transition metal complexes of the 1, 4(2'-hydroxyphenyl-1-yl) di-imino azine {1,4(2'HPDA)} are reported. The complexes have been characterized by elemental analysis, molar conductance, magnetic studies, IR, 1H NMR and UV-visible studies. They have the stoichiometry of the type [M{1,4(2'HPDA)}2 2H2O ] and [M'L2] where M= Mn(II), Fe(III), Co(II), Ni(II) and Cu(II), and M' = ZrO(II), VO(II), Zn(II), Cd(II), and Hg(II). The antibacterial and antifungal activity of the metal complexes has been investigated. Both ligand and complexes have shown good antibacterial and antifungal activity.